PD‐1 expression by canine T cells and functional effects of PD‐1 blockade. (25th January 2017) - Coy, J.; Caldwell, A.; Chow, L.; Guth, A.; Dow, S.
Abstract: The co‐inhibitory checkpoint molecule programmed death receptor 1 (PD‐1) can trigger T cell functional exhaustion upon binding to its ligand PD‐L1 expressed on tumour cells or macrophages. PD‐1 blocking antibodies have generated remarkable results in human cancer patients, including inducing durable responses in a number of advanced cancers. Therefore, monoclonal antibodies specific for canine PD‐1 were assessed for T cell binding and induction of functional activation. A total of 5–10% of CD4 T cells and 20–25% of CD8 T cells from healthy dogs expressed PD‐1, and PD‐1 expression was upregulated on T cells from dogs with cancer. Functionally, PD‐1 antibodies significantly enhanced T‐cell activation, as assessed by proliferation and interferon‐gamma (IFN‐γ) production. PD‐1 antibodies also reversed T‐cell suppression induced by canine soluble PD‐L1 and by tumour cells and tumour explant fragments. These findings indicate that PD‐1 antibodies have potential for use in cancer immunotherapy in dogs.